Self-Enforcing Peace Agreements that Preserve the Status Quo - Michelle R. Garfinkel; Constantinos Syropoulos (Center for Economic Studies and Ifo Institute (CESifo), 2021)
On the basis of a single-period, guns-versus-butter, complete-information model in which two agents dispute control over an insecure portion of their combined output, we study the choice between a peace agreement that maintains the status quo without arming (or unarmed peace) and open conflict (or war) that is possibly destructive. With a focus on outcomes that are immune to both unilateral deviations and coalitional deviations, we find that, depending on war's destructive effects, the degree of output security and the initial distribution of resources, peace can, but need not necessarily, emerge in equilibrium. We also find that, ex ante resource transfers without commitments can improve the prospects for peace, but only when the configuration of parameters describing the degree of output security and the degree of war's destruction ensure the possibility of peace without such transfers at least for some sufficiently even initial resource distributions.
Keywords: D30; D74; F51; 330; disputes; output insecurity; destructive wars; peaceful settlement; unarmed peace